Faecal pH throughout the reproductive cycle of sows in commercial pig herds. Issue 4 (19th April 2020) - Maes, Dominiek; Chantziaras, Ilias; Vallaey, Eline; Demeyere, Kristel; Meyer, Evelyne; Janssens, Geert P. J.
Abstract: Despite the importance of swine intestinal health, there are no easy‐to‐use and cost‐efficient methods to evaluate it under field conditions for sows. To provide some indication about intestinal health, pH of faeces could be used but reference values for the currently high‐performing commercial sow breeds are missing. In response, faecal pH of healthy sows from three different herds (herd A: 230 sows, herd B: 350 sows, herd C: 500 sows) was measured throughout the reproductive cycle. Within each herd, 10 sows were selected and rectal faeces samples were collected at different time points during the reproductive cycle: day 90 of gestation, day 1, 7, 14 and 21 of lactation, 7 days post‐weaning and day 30 of the next gestation. In addition, data on sow body condition (back fat), feed composition and coarseness of the feed were collected. For individual pH measurements, the pH ranged from 6.30 to 7.93. However, for all herds together, the average faecal pH value of the sows throughout the reproductive cycle ranged from 6.89 to 7.15. Also, the variations due to sow and time of sampling during the reproductive cycle were low with coefficients of variation of less than 5%. The results from the pairwise comparisons of the statistical model showed that in the last stages of lactation (i.e., at day 21), significantly lower average pH values ( p ≤ .05) are expected when compared to earlier stages of lactation (days 3 or 7), or at day 7 post‐weaning or compared to day 30 of the next gestation. Bearing its limitations, our study provided reference faecal pH values from high‐performing commercial sows under field conditions and as such they could be used directly in the field. Yet, further research is needed to provide more information on the factors affecting pH values throughout the reproductive cycle of the sow.